A angústia de Prometeu: a Crítica Literária e os conflitos de Harold Bloom - Lima, Luiz Fernando Martins de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present Doctoral Dissertation was written guided by three main aims, which are: to investigate the nature, statutes, limitations of and claims made by Literary Criticism and Theory; that being done, to carry out a survey of all the critical and theoretical publications by professor Harold Bloom (1930), from Yale University – eminent and controversial figure of Literary Studies nowadays – by means of expounding, collecting the wealth of critical acclaim of, and commenting on every work. The analysis of the twenty one books presented points out three predominant phases in the critic´s career: a phase in which studies of English Romanticism prevail, the phase of the development of the anxiety of influence theory, and the phase of the literary canon defense outside the Universities; at last, the third aim is to analyze one work of Criticism by each one of the phases pointed out – namely The Visionary Company (1961), Poetry and Repression (1976) and How to Read and Why (2000), respectively – in order to identify the foundations of Harold Bloom´s agonistic criticism and its rivals. By the end, it will be possible to verify that Harold Bloom´s critical performances always offered themselves as alternatives to major Literary Criticism trends that prevail or had prevailed in American Literary Studies: New Criticism, Deconstruction and Cultural Studies

A presente tese foi escrita orientada por três objetivos principais, quais sejam: investigar a natureza da Crítica e da Teoria Literária, expondo os seus estatutos, suas limitações e pretensões; dentro desse cenário, realizar o recenseamento de toda a produção crítica e teórica do professor Harold Bloom (1930), da Universidade de Yale – figura eminente e controversa dos Estudos Literários hoje – por meio da exposição, levantamento da fortuna crítica e comentário referente a cada uma das obras. A análise dos vinte e um livros apresentados aponta três fases predominantes na carreira do crítico norte-americano: uma fase em que predominam os estudos sobre o Romatismo inglês, a fase do desenvolvimento da teoria da angústia da influência e a fase da defesa do cânone literário fora das Universidades; por fim, o terceiro objetivo é analisar uma obra de Crítica Literária de cada uma das fases evidenciadas – a saber, The Visionary Company (1961), Poesia e Repressão (1976) e Como e por que ler (2000), respectivamente – de modo a identificar o fundamento da crítica agonística de Harold Bloom e seus rivais. Ao fim, será possível verificar que as performances críticas de Harold Bloom sempre se oferecem como alternativas às maiores correntes críticas que predominam ou já predominaram nos Estudos Literários norte-americanos: o New Criticism, a Desconstrução e os Estudos Culturais
Keywords: Bloom, Harold 1930; Critica; Literatura - História e critica - Teoria, etc; Literature